2022
DOI: 10.3390/geriatrics7060131
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Lifestyle Behavior, Goal Setting, and Personality among Older Adults: A Synthesis of Literature Reviews and Interviews

Abstract: Background: Despite the well-known health benefits of adopting a healthy lifestyle, older adults’ self-determination, goals, and motivation, as well as other personality factors, are known to influence their healthy lifestyle behaviors, yet these interactions have rarely been discussed. Method: The literature that investigated and discussed the interaction of personality, goals, and healthy lifestyle behaviors among older adults was reviewed. In addition, interview responses from older adults regarding their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
2
0
1
Order By: Relevance
“…Most subjects in this study were actively requested to use the facility, and their personalities, living environments, health literacy levels, and lifestyles may support the results of this study [ 41 ]. Recent studies showed that limited health literacy was associated with an increased risk of future frailty [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 92%
“…Most subjects in this study were actively requested to use the facility, and their personalities, living environments, health literacy levels, and lifestyles may support the results of this study [ 41 ]. Recent studies showed that limited health literacy was associated with an increased risk of future frailty [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 92%
“…Emphasizing self-regulation, goal-setting, and adherence to responsible drinking norms can be particularly effective in interventions targeting those with lower conscientiousness. By recognizing the protective nature of conscientiousness against problematic drinking, clinicians and researchers can develop strategies that harness these inherent traits, ultimately contributing to more effective approaches in preventing and addressing alcohol-related issues within diverse personality profiles [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
“…En cuanto al tipo de personalidad, 77 (68,1%) participantes tiene un nivel excelente, 22(19,5%) participantes tienen un nivel regular, 8 (7,1%) participantes tienen un nivel malo, 4 (3,5%) participantes tienen un nivel existe peligro y 2 (1,8%) participantes tienen un nivel bueno. Esta dimensión se refiere al humor y actitud para desarrollar actividades y el estudio, el tipo de personalidad establece conductas y estilos de vida en una persona(36) . Zegarra A(28) , señala que predomino el nivel excelente (57,6%) en esta dimensión.…”
unclassified